Does Pelvic Exam in the Emergency Department Add Useful Information? - Brown, Jeremy; Flemming, Rita; Aristizabal, Jamie; Gishta, Rocksolana (Western Journal of Emergency Medicine, 2011)
Objective: Physicians are taught that the pelvic exam is a key part of the evaluation of a woman presenting with abdominal pain or vaginal bleeding. However, the exam is time consuming and invasive, and its use in the emergency department (ED) has not been prospectively evaluated. We evaluated how often the findings of the pelvic exam changed management in a cohort of consecutive female patients presenting with acute abdominal pain or vaginal bleeding.Methods: We enrolled women who required a pelvic exam together with the providers caring for them in an academic ED from September 2004 to August 2005. We collected the results of the general history and physical exam. The provider was asked to predict the findings of the pelvic exam, and these were compared with the actual findings of the exam.Results: One hundred eighty-three patients were prospectively entered into the study. When compared with predicted findings, the pelvic exam was as expected in 131 patients (72%). In a further 40 patients (22%), the findings of the pelvic exam were not as predicted, but resulted in no change in the clinical plan. In 12 cases (6%) the exam revealed a finding that was both unexpected and changed the clinical plan. Only one of these patients was admitted. Of the 24 patients who were admitted, four had a pelvic exam that revealed unexpected results, but only one of these cases caused the physician to change the care planned for the patient.Conclusion: In 94% of women with acute abdominal pain or vaginal bleeding, the results of the pelvic exam were either predictable or had no effect on the clinical plan. This suggests that there may be a subset of women with abdominal pain or vaginal bleeding in whom a pelvic exam may safely be deferred. [West J Emerg Med. 2011;12(2):208-212.]